Rooting of jabuticabeira of cabinho mini-cuttings (Plinia trunciflora) - Hossel, Cristiano; Wagner Júnior, Américo; Hossel, Jessica Scarlet Alves de Oliveira; Fabiane, Kamila Cristina; Dallago, Adriana (Comunicata Scientiae, 2019)
The techniques of plant multiplication, when tested with native fruit trees, have proved to be limiting in several aspects, signaling that another technique should be tested, which might be recommended for the usage, especially in the jabuticaba trees which present a higher potential. The aim of this study was to test the usage of asexual propagation through mini-cuttings in jabuticabeira of cabinho according to the collection time, mini-cutting length and concentration of IBA. The work was performed at Federal Technological University of Paraná (UTFPR) – Campus Dois Vizinhos, Brazil. The samples were collected bimonthly. Mini-cuttings (6 or 8 cm) with pair of leaves reduced to 25% of the original size were prepared. The mini-cuttings had their base immersed in liquid solution of indole-butyric acid (0, 3000 and 6000 mg L-1) and placed in plastic tubes containing commercial substratum. The experimental design was completely randomized with 2 x 3 x 6 factorial (cutting length x IBA concentration x time of the year), with four replications, the experimental unit varied according to the number of shoots obtained. After 120 days of implementation of each collection, the parameters rooting and callogenesis (%), average number of roots per mini-cutting and average root length were evaluated. After 60 days the survival of post-planting rooted mini-cuttings was evaluated. It is recommended that for the jabuticabeira of cabinho, the collection period for propagation through mini-cuttings should be in August.